2016
DOI: 10.1093/chromsci/bmv248
|View full text |Cite
|
Sign up to set email alerts
|

QbD-Driven Development and Validation of a Bioanalytical LC–MS Method for Quantification of Fluoxetine in Human Plasma

Abstract: The current studies describe the Quality by Design (QbD)-based development and validation of a LC-MS-MS method for quantification of fluoxetine in human plasma using fluoxetine-D5 as an internal standard (IS). Solid-phase extraction was employed for sample preparation, and linearity was observed for drug concentrations ranging between 2 and 30 ng/mL. Systematic optimization of the method was carried out by employing Box-Behnken design with mobile phase flow rate (X1), pH (X2) and mobile phase composition (X3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In the HPLC method reported by Hasnain et al (), human plasma samples containing fluoxetine and the IS were subjected to SPE and evaporation–reconstitution processes for the whole preparation procedure, which significantly minimized matrix effects. The authors applied quality by design‐based principles and approaches into the discovery and optimization of the critical experimental parameters, thereby enhancing the understanding of the relationship and interactions between those parameters.…”
Section: Techniquesmentioning
confidence: 99%
“…In the HPLC method reported by Hasnain et al (), human plasma samples containing fluoxetine and the IS were subjected to SPE and evaporation–reconstitution processes for the whole preparation procedure, which significantly minimized matrix effects. The authors applied quality by design‐based principles and approaches into the discovery and optimization of the critical experimental parameters, thereby enhancing the understanding of the relationship and interactions between those parameters.…”
Section: Techniquesmentioning
confidence: 99%
“…BBD has an advantage over other designs that it requires less number of experiments, thus considerably saving time and effort [18, 19]. A score of research reports is the testimony of having demonstrated the utility of experimental designs in analytical method development [20–31]. For the present study survey of literature revealed that not a single bioanalytical method for ARIP assessed the robustness using the DoE approach which in turn may influence method performance over time.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, these techniques offer minimal data on how the different parameters listed above interact with, and ultimately influence, each other. In the past, research has been conducted on the development and application of retaliation surface methodologies for the quantification of various compounds [23][24][25][26][27][28][29][30][31][32][33][34]. Therefore, this research was focused on the development of a Box-Behnken-optimized RP-HPLC method for the quantification of domperidone and lansoprazole in new and unusual solvent systems.…”
Section: Introductionmentioning
confidence: 99%